BUSINESS PROCESS MANAGEMENT SYSTEM IMPLEMENTATION: A CASE OF A MICROFINANCE INSTITUTION IN COLOMBIA. - Pestana Tirado, Edwin Fernando (Archives of Business Research, 2019)
With increasing competition these days, many companies are now paying attention to support systems that enables quick decisions and transfer of information with shorter times. As a result, business process management (BPM) has become the most popular agenda to improve the basic functionalities of a company’s transactions This paper investigates the implementation of a Business Process Management System application known as “Smart Safe” for a Micro-financial institution in Colombia. The study was aimed at exploring answers to how BPM tools such as “Smart Safe”, technologies can successfully be implemented in a given MFI in Colombia. A case study approach was applied to collect information from Micro Finance Institutions (MFIs) in Colombia. The results showed that sub-stream BPM tools and techniques could be applied not only in MFIs but also in the other MFIs. It also showed that the software technology can be customised to the business process needs of other companies. Non-availability of a comprehensive reference source of MFIs, BPM tools, and expertise were the major issues encountered during the implementation and the training process. However, the proactive measures put in place by the National Board for Small Scale Enterprises (NBSEs) enabled many tasks to progress steadily than expected. The results also revealed that further consideration needs to be given to the development of Small Business Specific Implementation and Delivery Methodologies as well as supporting practitioner skill sets to enable this software application meet the demands of the MFIs in Colombia.